Is Histologic Thrombus Composition in Acute Stroke Linked to Stroke Etiology or to Interventional Parameters? - Goebel, J.; Gaida, B.-J.; Wanke, I.; Kleinschnitz, C.; Koehrmann, M.; Forsting, M.; Moenninghoff, C.; Radbruch, A.; Junker, A. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Detailed insight into the composition of thrombi retrieved from patients with ischemic stroke by mechanical thrombectomy might improve pathophysiologic understanding and therapy. Thus, this study searched for links between histologic thrombus composition and stroke subtypes and mechanical thrombectomy results.MATERIALS AND METHODS: Thrombi from 85 patients who had undergone mechanical thrombectomy for acute ischemic stroke between December 2016 and March 2018 were studied retrospectively. Thrombi were examined histologically. Preinterventional imaging features, stroke subtypes, and interventional parameters were re-analyzed. Statistical analysis was performed with the Kruskal-Wallis test, Mann-Whitney U test, or Spearman correlation as appropriate.RESULTS: Cardioembolic thrombi had a higher percentage of macrophages and a tendency toward more platelets than thrombi of large-artery atherosclerotic stenosis (P = .021 and .003) or the embolic stroke of undetermined source (P = .037 and .099) subtype. Thrombi prone to fragmentation required the combined use of contact aspiration and stent retrieval (P = .021) and were associated with an increased number of retrieving maneuvers (P = .001), longer procedural times (P = .001), and a higher lymphocyte content (P = .035).CONCLUSIONS: We interpreted the higher macrophage and platelet content in cardioembolic thrombi compared with large-artery atherosclerotic stenosis or embolic stroke of undetermined source thrombi as an indication that the latter type might be derived from an atherosclerotic plaque rather than from an undetermined cardiac source. The extent of thrombus fragmentation was associated with a more challenging mechanical thrombectomy and a higher lymphocyte content of the thrombi. Thus, thrombus fragmentation not only might be caused by the recanalization procedure but also might be a feature of a lymphocyte-rich, difficult-to-retrieve subgroup of thrombi.ESUSembolic stroke of undetermined sourceH&Ehematoxylin-eosinLAAlarge-artery atherosclerotic stenosisMTmechanical thrombectomymTICImodified TICIRBCred blood cellsWBCwhite blood cells